INTELLECTUAL PROPERTY AS FIDUCIARY OBJECT IN BANKING INSTITUTION - Setyawati Setyawati (Sultan Agung Notary Law Review, 2020)
Global Market Development today by the Industrial Revolution 4.0 brings influence to Intellectual Property (IP) in the fields of Economy, especially in getting loans at banks to increase the capital of a business, Intellectual Property (IP) is used as the object of Fiducia. Fiduciary Assurance Intellectual Exclusive Rights given a Act or regulation to a person or group of people for works of copyright under the Act so that Intellectual Property is right in Act-related issues Results of invention and Creativity person or persons relative to the Protection problems reputation in the field of commercial (commercial reputation) and action / services in the commercial field (goodwill). In the Global Market Development or the Industrial Revolution 4.0, the Intellectual Property (IP) can be made possible Fiducia. The guarantee proper object used in this case is Fiduciary. Setting Intellectual as Objects Fiduciary in Act Fiduciary not clearly regulated so that the necessary concept of ideal settings intellectual property as the object of Fiduciary must be developed by setting a comprehensive, systematic aspects of Substance, Structure, and Culture Act based on Pancasila and the Constitution Of the Republic of Indonesia Of 1945 in efforts to achieve economic development in Indonesia.